Therapeutic Intervention in Musculoskeletal Radiology: Current Practice and Future Directions - Walsh, John P.; Farrell, Terence P.; Hynes, John; Hughes, Nicola; O'Byrne, Ciara; Eustace, Stephen J. (Seminars in Musculoskeletal Radiology, 2018)
Over the last several decades, the volume and range of therapeutic musculoskeletal (MSK) interventions that radiologists can offer their patients has dramatically increased. With new materials and improving imaging modalities, as well as significant investment in research, the field of MSK interventional radiologic intervention will likely continue to expand. In this article, we summarize the range of interventions currently available to the MSK radiologist. We also seek to explore new and emerging techniques that may become commonplace in the near future while considering the challenges that may lie ahead in the field of MSK radiology.
Keywords: interventional radiology; musculoskeletal procedures; musculoskeletal radiology